The enrichment of hazardous elements, rare earth elements and other inorganic constituents in a thick coal seam of the Lower Indus Basin, Pakistan - Hassan Nasir Mangi; Liqiang Ma; Robert B. Finkelman; Detian Yan; Jing Li; Lara Sindhu; Umar Ashraf (International Journal of Coal Science & Technology)
Abstract The presence of inorganic constituents in coal is controlled by different geological factors, which, in turn, affect the technological, environmental, and health impacts of the coal. The main aim of this study is to objectively assess the mineralogical and geochemical characteristics of a thickest low-rank coal seam in the Lower Indus Basin southeastern Pakistan, and further investigate different controlling factors. The analytical results of major oxides, trace elements, and rare earth elements revealed that the weathering conditions were progressively variable and moderate. The sediment source, mainly of felsic and intermediate composition, was dominated by granitic rocks. The geochemical assessment reveals different depositional factors like marine environment influenced, while transitional and freshwater sediments influenced the center of the coal peat mire. Strontium, Zinc, and several hazardous trace elements, including Cu, Ni, Cr, and Co, have higher concentrations in these coals compared to world low-rank, U.S., and Chinese coals. The relatively higher concentration of Sr in the thick coal seam in the Lower Indus Basin, compared to other coals seams in Pakistan and the enrichment of Sr was primarily controlled by the denudation of crystalline rocks and marine influx in the coal-basin. The REY distribution pattern showed that enrichment of medium and heavy rare earth elements is higher than light rare earth elements in the coal seam. The Gd distribution pattern in the coal seam demonstrated that strong positive anomalies had a good affinity with paleo-acidic water concentration in the study area. The higher concentration of Sr and other elements enables a better assessment understanding of the coal geochemical history.